Verbal and Nonverbal Memory in Primary Progressive Aphasia: The Three Words-Three Shapes Test - Sandra Weintraub; Emily Rogalski; Emily Shaw; Sabrina Sawlani; Alfred Rademaker; Christina Wieneke; M.-Marsel Mesulam (Behavioural Neurology)
Objectives: To investigate cognitive components and mechanisms of learning and memory in primary progressive aphasia (PPA) using a simple clinical measure, the Three Words Three Shapes Test (3W3S).